2017
DOI: 10.29054/apmc/17.439
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Branching Pattern of Facial Nerve Seen in Adult Cadavers: An Anatomical Study

Abstract: Introduction: There are twelve cranial nerves and seventh one is the Facial cranial nerve, which supplies the muscles of facial expression. It gives of five terminal branches, which form a plexus with in the parotid gland. These branches exhibit variations in their branching pattern. Detection of the main trunk of facial nerve and its branches is important in all surgeries of this area, to avoid any injury that may lead to the loss of function of this nerve. This study has elaborated the branching and communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…5,7,9, [16][17][18]23 The third in place were types II, III, IV, and VI as was the observation in our population. 5, 7,9,12,[16][17][18]23,24 The branching pattern types VI, I, II, and V were the least frequent among Caucasians Indians, Pakistani, Thai, Koreans, Malaysians, and Arab similar to our study 5,7,9,17,19,22,24 . Types IV and VI occurred at the same frequency (15%) with the least being type V (5%) (►Table 1).…”
Section: Branching Patternssupporting
confidence: 81%
See 3 more Smart Citations
“…5,7,9, [16][17][18]23 The third in place were types II, III, IV, and VI as was the observation in our population. 5, 7,9,12,[16][17][18]23,24 The branching pattern types VI, I, II, and V were the least frequent among Caucasians Indians, Pakistani, Thai, Koreans, Malaysians, and Arab similar to our study 5,7,9,17,19,22,24 . Types IV and VI occurred at the same frequency (15%) with the least being type V (5%) (►Table 1).…”
Section: Branching Patternssupporting
confidence: 81%
“…17,18 In other reports from Thailand and India, types II and V were the highest, respectively. 19,24 Type I, the classical textbook pattern, was found to have been one of the least common patterns, which was not the case in this population. 23 The second most frequent in our population was type II (22.5%), like in Iraqi study.…”
Section: Branching Patternscontrasting
confidence: 56%
See 2 more Smart Citations
“…Thuku et al concluded type I as the most common in the African population [26]. Rana et al, Quadros et al, and Bendella & colleagues found type II as the most common in Pakistan, Indian, and German subjects, respectively [27-29] (Table 5).…”
Section: Discussionmentioning
confidence: 99%